2015
DOI: 10.1007/s11367-015-0849-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of life cycle assessment to sheep production systems: investigating co-production of wool and meat using case studies from major global producers

Abstract: Purpose Methodology of co-product handling is a critical determinant of calculated resource use and environmental emissions per kilogram (kg) product but has not been examined in detail for different sheep production systems. This paper investigates alternative approaches for handling coproduction of wool and live weight (LW, for meat) from dual purpose sheep systems to the farm-gate. Methods Seven methods were applied; three biophysical allocation (BA) methods based on protein requirements and partitioning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 28 publications
2
40
0
Order By: Relevance
“…LCA has been applied to all major ruminant production systems (beef, dairy, lamb and wool), albeit with different degrees of scrutiny into system-wide uncertainties. Frequently cited examples of works on the sheep sector include Biswas et al (2010), Ripoll-Bosch et al (2013) and Wiedemann et al (2015a). For dairy, Üçtuğ (2019) provides an extensive literature review encompassing 31 studies.…”
Section: Lca Applied To Ruminant Production Systemsmentioning
confidence: 99%
“…LCA has been applied to all major ruminant production systems (beef, dairy, lamb and wool), albeit with different degrees of scrutiny into system-wide uncertainties. Frequently cited examples of works on the sheep sector include Biswas et al (2010), Ripoll-Bosch et al (2013) and Wiedemann et al (2015a). For dairy, Üçtuğ (2019) provides an extensive literature review encompassing 31 studies.…”
Section: Lca Applied To Ruminant Production Systemsmentioning
confidence: 99%
“…However, several new allocation methodologies have been proposed for LCA studies of agricultural systems based on physical relationships between co-products. These methodologies are often referred to as Bbiophysical^allocation (International Dairy Federation 2010; Eady et al 2012;Thoma et al 2013;Gac et al 2014;Van Der Werf and Nguyen 2015;Wiedemann et al 2015). Draft guidelines on carbon footprinting in livestock systems issued by the FAO have also recommended that biophysical allocation should be adopted for models of the on-farm stages of livestock production (FAO 2014a;FAO 2014c), although currently not in the feed supply chain (FAO 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…This leaves a degree of ambiguity in the Higg MSI and potential inconsistencies in the underlying datasets and results. Having noted this, the review of primary data sources revealed a series of studies that had aims and methods consistent with attributional LCAs i.e., [49][50][51][52] and one study that had aims and methods consistent with consequential LCA [53].…”
Section: Choice Of Lca Methods and Implications For Handling Of Multi-mentioning
confidence: 99%